Analysis of Knowledge of Fertilization Employees on the Application of 4R’s Principle in Production Plant Fertilization Activities at Mutiara Estate PT. Sentosa Kalimantan Jaya - Juan Christhoperos; Jamaluddin; Arief Rahman; Puspita; Sukariyan (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Abstract To produce healthy and high-yielding oil palm plants, fertilization must be carried out. The application of fertilizer and the availability of nutrients in the soil greatly affect the growth and development of oil palm plants. Thus, a successful and precise fertilization strategy for oil palm is necessary during the fertilization process. To achieve this, the application of 4R (Four Rights) principles is required: Right dosage, Right type, Right location, and Right timing. This research aims to assess the level of understanding and knowledge among the employees of PT. Sentosa Kalimantan Jaya Estate Mutiara regarding fertilization, based on the 4R principles and the applicable fertilization SOP. The primary data used for this research consists of field activity observations conducted through observation and interviews, as well as secondary data sourced from the company. The secondary data were analyzed using quantitative descriptive analysis methods, which include the average values and percentages of the observation results. The research results indicate that employees understand the 4R principle of fertilization with an average of 81%. They also understand the right dosage at 94%, the right type at 89.67%, the right place at 92%, and the right timing at 83.67%.